2021
DOI: 10.3390/molecules26237359
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Preliminary Toxicity Evaluation of the Essential Oil from Peperomia circinnata Link var. circinnata. (Piperaceae) in Artemia salina Leach

Abstract: Peperomia Ruiz and Pav, the second largest genus of the Piperaceae, has over the years shown potential biological activities. In this sense, the present work aimed to carry out a seasonal and circadian study on the chemical composition of Peperomia circinata essential oils and aromas, as well as to evaluate the preliminary toxicity in Artemia salina Leach and carry out an in silico study on the interaction mechanism. The chemical composition was characterized by gas chromatography (GC/MS and GC-FID). In the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 71 publications
(77 reference statements)
0
25
0
Order By: Relevance
“…Therefore, we used this protein as a target in order to investigate the molecular interactions and the affinity energy formed in the HPPD-compounds complexes ( Figure 3 ). According to the literature, the majority are those compounds that have a concentration above 5% of the substance in the essential oil [ 77 , 78 , 79 , 80 , 81 ].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we used this protein as a target in order to investigate the molecular interactions and the affinity energy formed in the HPPD-compounds complexes ( Figure 3 ). According to the literature, the majority are those compounds that have a concentration above 5% of the substance in the essential oil [ 77 , 78 , 79 , 80 , 81 ].…”
Section: Resultsmentioning
confidence: 99%
“…These variations in the chemical compositions of essential oils obtained from different plant parts were supposed because of the direct contact with sunlight with HCCAO (aerial part), nonavailability of sunlight to HCCRO (rhizome), and different type of physiology in both type of plant parts. In other works, authors have reported that the chemical composition of essential oils can be affected by the presence of light, time of year, rain, dry weather, and circadian rhythm, among other factors [ 16 , 17 , 18 ]. The GC-MS profile and the detailed comparative chemical composition of HCCAO and HCCRO are represented in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The search for new phytotherapeutics with anticancer (tumor) potential is extremely important because most anticancer drugs are of natural origin. Natural products have a high level of efficacy in use and application, constituting the main ally in the preparation and development of new treatments for cancer [ 86 , 87 ]. In this industry, the essential oils from botanical species of the Amazon region have shown favorable cytotoxic activity and applications, as reported in prior studies [ 38 , 88 , 89 ], in which the essential oils of two species of Eugenia ( E. cuspidifolia and E. tapacumensis ) collected in the forest reserve Adolfo Ducke, Manaus, Amazonas, Brazil, were assessed against five types of cancer cells: human malignant melanoma (SK-MEL-19), human colorectal carcinoma (HCT116), human breast adenocarcinoma (MCF7), human gastric adenocarcinoma (ACP02), and human embryonic lung (MRC-5 as a non-malignant cell line).…”
Section: Biological Activities Of Essential Oils From the Amazon Regionmentioning
confidence: 99%